Rice bean (Vigna umbellata) – A Potential Legume under Adverse Conditions - Vikram, Nalabolu; Sarkar, Narayan Chandra (International Journal of Bio-resource and Stress Management, 2022)
Rice bean is an underutilized legume crop that comes up with many benefits i.e., dried pulse, fodder and green manure thus helps in human, animal nutrition and environmental health. It is a resilient plant that is resistant to a variety of diseases and pests especially to the Bruchids, it can be grown well in less fertile, exhausted, degraded lands and drought prone sloping areas; along with these, Rice bean contains genes for biotic and abiotic stress tolerance, including drought, soil acidity tolerance especially for Aluminum ions. Waterlogging shows a greater negative impact on crops especially on legumes by reducing photosynthesis, plant growth, grain yield; formation, function and survival of nodules, biological nitrogen fixation, and may even causes plant death in severe waterlogged conditions. An insufficient supply of nitrogen or carbohydrates is thought to have hampered flowering plant life and recovery. Waterlogging at any stage has a detrimental impact on seed output. Depending on the conditions, flooding stress can range from transient to permanent. Based on the sort of flooding regime in the habitat, different species, or even different genotypes of the same species, choose an avoidance, escape, or quiescence strategies to overcome stress, among these coping options Rice bean may follow morphological alterations in the escape mechanism. As Rice bean can thrive well in adverse conditions and even in waterlogged conditions, once the exact reason behind this tolerance is explored, that feature can be used in breeding programs for crop improvement.